Decreasing costs of renewables: Implications for Mexico's climate targets - Johannes Eckstein; Jose Antonio Ordonez; Jakob Wachsmuth (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
The unconditional target of Mexico's NDC foresees a reduction of GHG emissions of 22% relative to a Business-as-Usual (BAU) scenario, to reach 762 MtCO2eq in 2030. It further specifies that specifies that electricity generation shall take a share of 30% of this mitigation effort to reduce emissions by 31.4% relative to BAU, reaching 139 MtCO2eq in 2030. This study analyses how falling cost projections of renewable energy technologies (solar PV and wind energy) could inform energy sector and climate change mitigation plans of Indonesia. We show that cost projections valid for Mexico for renewables have dramatically fallen over the past years. Costs projected for 2030 a couple of years ago are well undercut by more recent projections for 2030. Recent cost projections for 2030 for wind energy are 77% lower than projections dating from 2015, solar PV cost projections have fallen by 74% on average. If falling costs for renewables are considered, the renewable capacities given in PRODESEN (the national power sector plan) could be revised at constant investments. The overall renewable energy capacity given in PRODESEN for 2030 could be increased from 37 GW to 52 GW. This increase in renewable capacities could inform the revision of Mexico's NDC. If falling cost projections of renewable energies are considered, the unconditional target could be reduced from 762 MtCO2eq to 747 MtCO2eq at constant costs. This corresponds an increase from 22% to 23.5% reduction and presents a 23.4% increase in the ambition of the power sector. Further Reading In a companion paper, Eckstein et al. (2020a) discuss the processes and assumptions underlying the current revision of the NDC in Mexico. Based on Interviews, they discuss the roles of the different institutions responsible for energy and climate mitigation plans, their policy and planning instruments and the relationship between these. Within the same project, the team of authors has written two more studies of the same structure for Indonesia (Eckstein et al. 2020b, Ordonez and Eckstein 2020) and Argentina (Nascimento et al.2020, Kurdziel et al.2020).
urn:nbn:de:0011-n-6156267
Keywords: 330